Dual techniques for trace copper determination: DES/Dithizone based liquid phase microextraction-flame atomic absorption spectrophotometry and digital image based colorimetric probe - Kilinc, Yagmur; Zaman, Buse Tugba; Bakirdere, Sezgin; Ozdogan, Nizamettin (ELSEVIER SCI LTD, 2024)
In this study, a sample preparation procedure was developed to preconcentrate copper ions from aqueous samples for determination by flame atomic absorption spectrometry (FAAS) and digital image based colorimetry (DIC) systems. This was achieved by complexing copper ions with dithizone (Cu-DZ) and extracting the complex from aqueous solution in a single step. For the DES/DZ-FAAS system, a low detection limit of 2.3 ng mL-1 was recorded over a broad and linear working range. For the DIC system, the linear relationship between the change in red color intensity of the red-green-blue (RGB) color scale and the concentration of copper in the Cu-DZ complex was utilized for the validation of the method. The DIC system also recorded a broad and linear working range with a satisfactory detection limit of 14.7 ng mL-1. Spike recovery experiments performed with eucalyptus tea extracts yielded high recovery results in the range of 91-107%.
Keywords: Copper; Deep eutectic solvent; Dithizone; Eucalyptus tea extracts; Liquid phase microextraction; WASTE-WATER; METAL-IONS; LIGAND; PRECONCENTRATION; ADSORPTION; CHLORIDE; BIOMASS; Chemistry; Food Science & Technology; Nutrition & Dietetics